ChemInform Abstract: Taming Hypervalent Bonds and Strained Rings for Catalysis and Synthesis. Issue 41 (October 2015) - de Nanteuil, Florian; Li, Yifan; Vita, Maria Victoria; Frei, Reto; Serrano, Eloisa; Racine, Sophie; Waser, Jerome
Abstract Review: 54 refs.